Defense system, craft, and Society in the New Kingdom of Granada eighteenth century. The case of Cartagena de Indias, 1750-1810 (2013)
This article is part of a historiographical perspective complicate interested in a more detailed study of late colonial society. It analyzes the processes of construction and maintenance of the defense system of Cartagena, the workers engaged in such work, and occupational social hierarchies among these, the difficulties this imposed on the development of the life of the guilds, and as the end of Colony exaltation of the virtues of work went parallel with new ways of reading the social setting of the city, leading many craftsmen were recognized as virtuous.